2014
DOI: 10.1371/journal.pone.0107871
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Changes of the Corpus Callosum in Congenital Blindness

Abstract: We examined the effects of visual deprivation at birth on the development of the corpus callosum in a large group of congenitally blind individuals. We acquired high-resolution T1-weighted MRI scans in 28 congenitally blind and 28 normal sighted subjects matched for age and gender. There was no overall group effect of visual deprivation on the total surface area of the corpus callosum. However, subdividing the corpus callosum into five subdivisions revealed significant regional changes in its three most poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 57 publications
(72 reference statements)
0
36
0
1
Order By: Relevance
“…In contrast, the only reports of increases in white matter volume were observed in sensorimotor cortex [87] and evidence of increased white matter integrity within the cortical spinal tract [88]. Regional changes were also reported within the corpus collosum [35, 44]. Using a whole brain analysis approach, Shu and colleagues (2009) (employing DTI) reported an overall decrease in white matter connectivity in the blind including connections between occipital and inferior frontal areas [43, 86].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the only reports of increases in white matter volume were observed in sensorimotor cortex [87] and evidence of increased white matter integrity within the cortical spinal tract [88]. Regional changes were also reported within the corpus collosum [35, 44]. Using a whole brain analysis approach, Shu and colleagues (2009) (employing DTI) reported an overall decrease in white matter connectivity in the blind including connections between occipital and inferior frontal areas [43, 86].…”
Section: Discussionmentioning
confidence: 99%
“…These interpretation fits well with the finding that neuronal activity promotes oligodendrogenesis and increases myelination (Gibson et al, 2014). Another study examined the CC in a cohort of congenitally blind individuals (Tomaiuolo et al, 2014). The authors found that the splenium was significant smaller in blind subject as compared to control.…”
Section: Callosal Plasticity: How Visual Input Impacts On Interhemispmentioning
confidence: 99%
“…The optic nerves, lateral geniculate nucleus, and pericalcarine white matter are reduced in volume [14], as is the splenium of the corpus callosum, which connects the hemispheres of the visual cortex [5, 6]. While the surface area of primary visual cortex is reduced [7, 8], the gray matter layer of this area is thickened [710], perhaps reflecting altered synaptic pruning during cortical maturation [11, 12].…”
Section: Introductionmentioning
confidence: 99%